2015
DOI: 10.1103/physrevlett.114.036402
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Black Hole in a Stationary Hydrodynamic Flow of Microcavity Polaritons

Abstract: We report an experimental study of superfluid hydrodynamic effects in a one-dimensional polariton fluid flowing along a laterally patterned semiconductor microcavity and hitting a micron-sized engineered defect. At high excitation power, superfluid propagation effects are observed in the polariton dynamics; in particular, a sharp acoustic horizon is formed at the defect position, separating regions of sub- and supersonic flow. Our experimental findings are quantitatively reproduced by theoretical calculations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
185
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(191 citation statements)
references
References 34 publications
4
185
1
1
Order By: Relevance
“…4 Refined etching and microstructuring techniques have been developed for GaAs-based microcavity, allowing the fabrication of high quality micropillars, 5,6 mesas, 7 as well as advanced polaritonic circuits elements like waveguides, interferometers, optical gates, [8][9][10] and lattices with direct applications for quantum simulations. [11][12][13][14][15] This approach is likely to be successful in the upcoming years; however, for practical use, its drawback is to be stuck to cryogenic temperatures. A way around this problem is the use of large bandgap materials, where the exciton binding energy is larger, and hence stable at room temperature.…”
mentioning
confidence: 99%
“…4 Refined etching and microstructuring techniques have been developed for GaAs-based microcavity, allowing the fabrication of high quality micropillars, 5,6 mesas, 7 as well as advanced polaritonic circuits elements like waveguides, interferometers, optical gates, [8][9][10] and lattices with direct applications for quantum simulations. [11][12][13][14][15] This approach is likely to be successful in the upcoming years; however, for practical use, its drawback is to be stuck to cryogenic temperatures. A way around this problem is the use of large bandgap materials, where the exciton binding energy is larger, and hence stable at room temperature.…”
mentioning
confidence: 99%
“…Until recently, proposed analog systems to test Hawking's prediction by experiments suffered from a low characteristic temperature [3,[6][7][8][9][10][11][12]. In 2008, Philbin et al [13] demonstrated the feasibility of creating artificial event horizons with a moving refractive-index front (RIF) in dispersive optical media.…”
Section: Introductionmentioning
confidence: 99%
“…This pioneering work opened the door to the study of gravitational problems in the laboratory, and since then, many analog setups have been proposed in systems as different as Fermi gases [5], ion rings [6], polaritons [7] or, in a classical context, surface waves in a water tank [8].…”
Section: Introductionmentioning
confidence: 99%